Assistance Current Effect for Prevention of Voltage Reversal in Stacked Microbial Fuel Cell Systems. Issue 5 (11th February 2015) - Kim, Bongkyu; Lee, Byung‐Geun; Kim, Byung Hong; Chang, In Seop
Abstract Herein, an assistance current is suggested as a new approach to prevent voltage reversal in series‐connected microbial fuel cells (MFCs). This approach can be used to revive reversed MFCs, as a supporting assistance current is applied through an assistance anode when voltage reversal occurs. However, when the assistance current is applied without control over the assistance current, voltage reversal is regenerated. Therefore, to control the assistance current, the suggested approach is complemented by the application of variable resistors between the anode and assistance electrode. As a result, the regenerated voltage reversal is restored and all voltages of MFC units in the stacked MFC remain positive. Thus, it is expected that this approach could resolve voltage reversal that occurs in series‐connected MFCs, and thus increase the applicability of MFC technology to the production of practically usable electricity, with potential for extension to large‐scale MFCs.